High-resolution H α imaging of the northern Galactic plane and the IGAPS image database - Greimel, R.; Drew, J. E.; Monguió, M.; Ashley, R. P.; Barentsen, G.; Eislöffel, J.; Mampaso, A.; Morris, R. A. H.; Naylor, T.; Roe, C.; Sabin, L.; Stecklum, B.; et al. (Astronomy and astrophysics (Berlin), 2021)
The INT Galactic Plane Survey (IGAPS) is the merger of the optical photometric surveys IPHAS and UVEX based on data from the Isaac Newton Telescope (INT) obtained between 2003 and 2018. It captures the entire northern Galactic plane within the Galactic coordinate range | b |< 5° and 30° < ℓ < 215°. From the beginning, the incorporation of narrow-band H α imaging has been a unique and distinctive feature of this effort. Alongside a focused discussion of the nature and application of the H α data, we present the IGAPS world-accessible database of images for all five survey filters, i , r , g , U RGO , and narrow-band H α , observed on a pixel scale of 0.33 arcsec and at an effective (median) angular resolution of 1.1−1.3 arcsec. The background, noise, and sensitivity characteristics of the narrow-band H α filter images are outlined. Typical noise levels in this band correspond to a surface brightness at full ∼1 arcsec resolution of around 2 × 10 −16 erg cm −2 s −1 arcsec −2 . Illustrative applications of the H α data to planetary nebulae and Herbig-Haro objects are outlined and, as part of a discussion of the mosaicking technique, we present a very large background-subtracted narrow-band mosaic of the supernova remnant Simeis 147. Finally, we lay out a method that exploits the database via an automated selection of bright ionised diffuse interstellar emission targets for the coming generation of wide-field massive-multiplex spectrographs. Two examples of the diffuse H α map output from this selection process are presented and compared with previously published data.